Direct neutrino-mass measurement with sub-electronvolt sensitivity - Aker, Max; Rodejohann, Werner; Spanier, Felix (Nature physics, 2022)
Since the discovery of neutrino oscillations, we know that neutrinos have non-zero mass. However, the absolute neutrino-mass scale remains unknown. Here we report the upper limits on effective electron anti-neutrino mass, mν, from the second physics run of the Karlsruhe Tritium Neutrino experiment. In this experiment, mν is probed via a high-precision measurement of the tritium β-decay spectrum close to its endpoint. This method is independent of any cosmological model and does not rely on assumptions whether the neutrino is a Dirac or Majorana particle. By increasing the source activity and reducing the background with respect to the first physics campaign, we reached a sensitivity on mν of 0.7 eV c-2 at a 90% confidence level (CL). The best fit to the spectral data yields $${{}}{m}_{ν }^{2}{{}}$$ = (0.26 ± 0.34) eV2 c-4, resulting in an upper limit of mν < 0.9 eV c-2 at 90% CL. By combining this result with the first neutrino-mass campaign, we find an upper limit of mν < 0.8 eV c-2 at 90% CL.
Das PDF enthält zusätzlich einen Anhang von 11 Seiten
The KATRIN collaboration: M. Aker, F. Spanier, W. Rodejohann [und weitere 131 Verfasser]
Gesehen am 23.03.2022